Low-dose thioperamide injected into the cerebellar vermis of mice immediately after exposure to the elevated plus-maze impairs their avoidance behavior on re-exposure to the apparatus - Costa Neto,J. (2013)
The present study investigated the effect of thioperamide (THIO), an H3 histaminergic receptor antagonist, microinjected into the cerebellar vermis on emotional memory consolidation in male Swiss albino mice re-exposed to the elevated plus-maze (EPM). We implanted a guide cannula into the cerebellar vermis using stereotactic surgery. On the third day after surgery, we performed behavioral tests for two consecutive days. On the first day (exposure), the mice (n=10/group) were exposed to the EPM and received THIO (0.06, 0.3, or 1.5 ng/0.1 µL) immediately after the end of the session. Twenty-four hours later, the mice were re-exposed to the EPM under the same experimental conditions, but without drug injection. A reduction in the exploration of the open arms upon re-exposure to the EPM (percentage of number of entries and time spent in open arms) compared with the initial exposure was used as an indicator of learning and memory. One-way analysis of variance (ANOVA) followed by the Duncan post hoc test was used to analyze the data. Upon re-exposure, exploratory activity in the open arms was reduced in the control group, and with the two highest THIO doses: 0.3 and 1.5 ng/0.1 µL. No reduction was seen with the lowest THIO dose (0.06 ng/0.1 µL), indicating inhibition of the consolidation of emotional memory. None of the doses interfered with the animals' locomotor activity. We conclude that THIO at the lowest dose (0.06 ng/0.1 µL) microinjected into the cerebellum impaired emotional memory consolidation in mice.